Mutagenic study of benzimidazole derivatives with (+S9) and without (−S9) metabolic activation - Azahar, Nurul Hafizan; Ab Dullah, Siti Soleha; Abdullah, Rozaini; Ahmat, Norizan; Md. Akim, Abdah; Ab. Hamid, Hasiah (MDPI, 2019)
Benzimidazole derivatives have a diverse range of biological activities, including antiulcer, antihypertensive, antiviral, antifungal, anti-inflammatory, and anticancer. Despite these activities, previous studies have revealed that some of the derivatives can induce mutations. This study aimed to screen for potential mutagenic activities of novel benzimidazole derivatives 1–4 using the Ames test and to study their structure–activity relationship (SAR). An Ames test was carried out on two strains of Salmonella typhimurium (TA98 and TA100) in the absence and presence of metabolic activation. Genetic analysis was performed prior to the Ames test to determine the genotypes of the bacterial tester strains. Both bacterial strains showed dependency on histidine with the presence of rfa mutation, uvrB deletion, and plasmid pKM101. Further, all derivatives tested showed no mutagenic activity in the absence of metabolic activation in both tester strains. However, in the presence of metabolic activation, compound 1 appeared to induce mutation at 2.5 µg/plate when tested against the TA98 strain. These results suggest that the absence of the -OH group at the ortho-position over the phenyl ring might be the cause of increased mutagenic activity in compound 1. Additionally, the presence of mutagenic activity in compound 1 when it was metabolically activated indicates that this compound is a promutagen.